Who Governs in Deep Crises?: The Case of Germany. Issue 2 (1st December 2020) - Merkel, Wolfgang
Abstract: The Berlin Republic of today is neither Weimar (1918–1932) nor Bonn (1949–1990). It is by all standards the best democracy ever on German soil. Nevertheless, during the COVID-19 crisis there was a shift from democracy as a mode of governance to what the controversial legal theorist Carl Schmitt (1922) affirmingly described as a "state of exception"; a state that is desired and approved by the people (through opinion polls). It was the hour of the executive. The parliament disempowered itself. There was very little, if any, contestation or deliberation during the first eight weeks of the COVID-19 crisis. This article reflects on the implications of this mode of governance on institutions and actors of democracy in Germany, and offers a way of assessing the wellbeing of democracies in times of deep crisis.